Supervision of the Anti-Money Politics Movement (GAPU) as Civil Society in Berau’s 2024 Regional Elections - Arief Fadillah; Muhammad Hairul Saleh (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2025)
The issue of money politics in local elections remains a critical challenge to the consolidation of democracy in Indonesia. Previous studies have largely focused on the institutional role of Bawaslu as the state’s formal election supervisory body, leaving a gap in understanding how local civil society organizations conduct independent oversight. This study fills that gap by examining the Gerakan Anti Politik Uang (GAPU) as a civil society movement in Berau Regency during the 2024 Regional Election. The main research question is: How does GAPU conduct democratic oversight, how effective is it, and what challenges does it face? Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, presentation, and conclusion drawing. The findings reveal that GAPU performs oversight through public education, collaboration with Bawaslu, and social media campaigns, making it an effective but still fragile form of civic monitoring. Its weaknesses include limited resources, financial transparency, and potential elite co-optation. The study’s novelty lies in positioning GAPU as a local model of participatory democratic oversight that complements formal institutions. Practically, this research recommends strengthening cooperation between GAPU, Bawaslu, and law enforcement agencies to institutionalize participatory oversight and ensure sustainable, transparent, and independent democratic monitoring at the local level.